AKIBAT HUKUM PENOLAKAN KOREKSI KLAIM PATEN BERDASARKAN UNDANG-UNDANG PATEN: Legal Consequences of Refusal of the Correction of Patent Claims Under the Patent Law - Noor Alvy Bintang; Aline Gratika Nugrahani (Faculty of Law, Universitas Trisakti, 2025)
Patent protection arises when the discovery or invention is registered. In this registration there is an administrative and substantive examination process. If the application meets the requirements, then the application for registration of the invention is accepted. During the registration process, inventors can also submit corrections to their patent claims to be corrected if the patent claim contains errors in the description of the patent claim. However, sometimes applications for correction of patent claims are rejected by the Patent Appeals Commission because they do not meet the administrative or substantive requirements in the application. This article will discuss the legal consequences of rejecting an application for correcting patent claims for an invention, using normative research methods. The result and conclution of this article shows that the legal consequence of rejecting a claim correction is that a patent claim that has been submitted and accepted remains valid in its original form, without any changes or corrections, the patent holder loses the opportunity to correct errors or ambiguities in the claim which could lead to disputes in future.